The Improvement of Science Teacher Competence and Quality in Schools: A Theoretical and Practical Review - Prananda, Gingga; Refariza, Elva (TOFEDU: The Future of Education Journal, 2025)
This study aims to analyze efforts to improve the competence and quality of science teachers in Indonesia by examining educational regulations, teacher training programs, and the utilization of technology in teaching. Using a literature review approach, data were collected from scholarly articles, books, policy reports, and previous studies related to the professional development of science teachers. The results of the study show that although regulations and teacher certification programs are in place, their implementation remains uneven across Indonesia, especially in remote areas. Many science teachers still rely on traditional teaching methods, which hinder the development of students' critical thinking skills. Additionally, technology-based training has great potential but is constrained by infrastructure limitations, such as unequal access to the internet. In conclusion, more inclusive policies, improved training based on pedagogical skills, and investment in infrastructure are necessary to support the equitable and sustainable development of science education quality in Indonesia.